An investigation on workload indicator of staffing need: A scoping review - Farzaneh Doosty; Mohammad R Maleki; Mohammad H Yarmohammadian (Wolters Kluwer Medknow Publications, 2019)
The purpose of this scoping review was to survey the most recent (10 years) estimating of needed human resource in health-care organization by Workload Indicators of Staffing Need (WISN) method literature to understand themes and research avenues that may be helpful and beneficial to estimating of needed staff in health-care organizations. Our search strategy was based on using search engines such as Medline, Google Scholar, Scopus, and PubMed as well publications such as Elsevier, Emerald, ProQuest, and Springer. Finally, 31 articles extract for scoping review. Scoping review findings emerge in four key points that mentioned as follow: Service delivery time, Geographical features, Workload, and Supply and Demand. Furthermore, the strengths and weakness of WISN extracted from literature. As conclusion, the WISN method is applicable to any health-care organization, and of course, in smaller institutions, it can be done more quickly and efficiently. Where shortages of staff were identified using WISN, and if increasing the number of employees was impossible, we could use the task shifting. WISN can be used to calculate the required human resources for future models based on some assumptions such as the results of staff training, demographic changes, and disease profiles and staff turnover.